2021
DOI: 10.1002/hep4.1800
|View full text |Cite
|
Sign up to set email alerts
|

Globo H Is a Promising Theranostic Marker for Intrahepatic Cholangiocarcinoma

Abstract: Recent studies support the development of cancer therapeutics to target Globo H-ceramide, the most prevalent tumorassociated carbohydrate antigen in epithelial cancers. Herein, we evaluated the expression of Globo H and its prognostic significance in intrahepatic cholangiocarcinoma (ICC) and conducted preclinical studies to assess the antitumor activity of Globo H-specific antibody in thioacetamide (TAA)-induced ICC in rats. Globo H-ceramide in tumor specimens was detected by immunohistochemistry (IHC) and mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This is consistent with our previous report that high expression of B3GALT5 and FUT1, key biosynthetic enzymes for SSEA3 and Globo H, is an independent predictor for the survival of HCC patients [ 12 ]. Similarly, Globo H expression is a poor prognostic indicator in intrahepatic cholangiocarcinoma [ 36 ]. In addition, we showed association of Globo H expression with vascular invasion in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with our previous report that high expression of B3GALT5 and FUT1, key biosynthetic enzymes for SSEA3 and Globo H, is an independent predictor for the survival of HCC patients [ 12 ]. Similarly, Globo H expression is a poor prognostic indicator in intrahepatic cholangiocarcinoma [ 36 ]. In addition, we showed association of Globo H expression with vascular invasion in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal fucosylated GSLs including Globo H were identified by mass spectrometry in HCC in a previous study [ 43 ], consistent with our findings by immunohistochemistry. Indeed, we showed significant therapeutic efficacy of a Globo H antibody in rats with thioacetamide-induced cholangiocarcinoma [ 36 ]. Moreover, in a phase II clinical trial of Globo H-KLH vaccine in breast cancer, those patients who mounted Globo H-specific IgG and IgM antibodies had significantly better progression free survival [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have suggested that enhancing NK cell function or increasing the numbers of NK cells delays CCA progression, which may be a potential therapeutic target for CCA. Anti-Globo H antibody VK9 can enhance the activation and increase the presence of NK cells in the TIME, resulting in the inhibition of iCCA rat tumor growth ( 69 ). In vitro studies have demonstrated that the cytotoxic effect of activated NK cells on CCA cell lines may be augmented by cetuximab and cordycepin, effectively restraining CCA cell growth ( 70 , 71 ).…”
Section: Tumor Immune Microenvironment Of Cholangiocarcinomamentioning
confidence: 99%
“…Existing research has suggested that CCA cells can induce the apoptosis of CD4 + , CD8 + T cells and CD56 + NK cells via the Fas/FasL pathway to produce immune evasion 75 . To study how to maintain or increase the antitumor activity of NK cells, Hung et al constructed a thioacetamide (TAA)-induced rat ICC model and suggested that the anti-Globo H antibody VK9 can facilitate the activation of NK cells in the tumor microenvironment, increase the Direct cytotoxicity and enhance ADCC function 76 . Panwong et al have suggested that cordycepin can increase the anti-CCA activity of NK-92, and TRAIL signaling may play a role in the immune regulation process of cordycepin 77 .…”
Section: Advances Of Immune Cells In Ccamentioning
confidence: 99%